Рецепция творчества Андрея Платонова в Воронеже: к проблеме формирования „локальных текстов” - Nikonowa, Tamara (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
The article considers the process of studying Andrei Platonov’s literary work on his native land. The process is examined in light of today’s topic of literary criticism concerning studying “local texts” which insert the regional tradition into the national structure context.
An interpretation of Andrei Platonov’s literary work in Voronez: on the problem of research on „local texts”
Recepcja twórczości Andrieja Płatonowa w Woroneżu: problem kształtowania „tekstów lokalnych”